PENGARUH PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, DAN INVESTMENT OPPORTUNITY SET TERHADAP STRUKTUR MODAL - Septiani, Mira; Wulandari, Endang (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
This study aims to see the effect of sales growth, company size and investment opportunity set on the capital structure Secondary data is used for research and collected using purposive sampling. The data was then analyzed using multiple linear regression. The results showed that R, which amounted to 0.331. This means that the variation of all independent variables can affect changes in the dependent variable by 0.331 (33.1%). While the remaining 66.9% is influenced by other variables outside this study. The coefficient has a significant value of sales growth variable research is 0.225> 0.05, meaning that partially the effect is not significant. The significant value of the company size variable research is 0.310> 0.05, meaning that partially it has no significant effect and the significance value of the investment opportunity set (IOS) variable research is 0.002 <0.05, meaning that partially it has a significant effect. Therefore, sales growth and firm size have no effect on capital structure. Meanwhile, investment opportunity set affects the capital structure. The limitation of this research is the lack of research period on the small sample used.